Hazardous Area Classification Assessment at a Pharmaceutical Industry in East Jakarta - Eky Susilowati; Fatma Lestari (Universitas Airlangga, 2023)
Introduction: Fire is a common risk in any industrial facility that uses combustible and flammable raw materials, products, or supporting materials. Among others, the pharmaceutical industry is exposed to such risk due to the application of flammable liquids including ethanol as a volatile solvent in production areas, which has the potential to form explosive atmospheres through evaporation from pools created by accidental releases. Therefore, this study aims to analyze the hazardous area classification (HAC) in ethanol storage areas to facilitate the execution of risk mitigation efforts for reducing the role of ignition sources that cause fire and explosion. Methods: The HAC assessment was carried out in December 2021 - January 2022 using the quantitative method outlined in the International Electrotechnical Commission (IEC) standard: IEC/EN 60079-10-1 for zone determination. During flash point analysis, the ASTM D-93 method was employed to define the class of ethanol as a flammable liquid. Results: The ethanol storage areas fell into the zone 2 category based on the secondary grade of release, as well as the areas' ventilation effectiveness with a medium dilution, and fair ventilation availability. The extent of zone 2 is up to 3 m from the release source. Conclusion: Ignition sources capable of leading to fire and explosion incidents in ethanol storage areas should be controlled.